Early roman hoard from Mačvanska Mitrovica (?): Contribution to the precious silver metal working cultural koiné - Guštin Mitja; Popović Ivana (Starinar, 2017)
In 2014, a group of silver objects was sold with the accompanying data “from Serbia, from the area of Mačvanska Mitrovica”, which, based on their composition, belonged to a hoard of the Early Roman period. The hoard of silver objects contains a total of 21 pieces that can be divided into 10 different types: emblemata, belt plates, tubuli, torques, wire jewellery - a bracelet and rings, necklaces of the chain type, rings, pendants of lunula, rhomboidal and omega shape, bracelet and rings with pendants in the form of miniature axes. The composition of the silver objects in the Mačvanska Mitrovica (?) hoard show surprising similarities with the rich hoards of silver jewellery of Bare, Tekija and the find from Radenković-Crkvine and also with the distant hoard from Oltenia in the site of Rovinari (once Poiana, county Gorj). Therefore, we have named this group the Tekija - Bare hoards horizon, after two well-known most representative hoard-contents and their position in the middle of this geographical region. The last denarii from the Tekija and Bare hoards where minted at the end of AD 81, which allows the conclusion that these hoards, found near the military camps of Transdierna and Viminacium, were probably deposited in the years after AD 81, during the restless period of Roman-Dacian conflicts. In the Mačvanska Mitrovica (?) hoard and the Radenković-Crkvine find the monetary part did not exist, so the time of their depositing remains open. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 177007: Romanisation, urbanisation and transformation of urban centres of civil, military and residential character in Roman provinces in the territory of Serbia]